The Influence of Corporate Entrepreneurship on MSME Business Performance: The mediating role of Entrepreneurial Collaborative Capability - Sumarni, Sumarni; Chairunnisa, Fitri; Malinda SB, Istiqomah; Siregar, Ade Perdana (Dinasti International Journal of Management Science, 2025)
The growth of MSMEs should be a central focus for various stakeholders, particularly the government, as MSMEs play a vital role in driving economic growth in Indonesia, especially at the regional level such as in Jambi Province. In 2023, MSMEs in Jambi Province experienced a decline, which poses a potential threat to regional economic growth. Given this context, the performance of MSMEs must be prioritized to ensure their resilience also capacity for sustainable growth. Achieving optimal performance in meeting organizational objectives requires the implementation of corporate entrepreneurship. However, for corporate entrepreneurship to effectively enhance business performance, it must be supported by the entrepreneurial collaborative capability of business owners.A review of existing literature indicates a lack of studies investigating MSME business performance influenced by corporate entrepreneurship through the mediating role of entrepreneurial collaborative capability. Accordingly, this study aims to: (1) examine the effect of corporate entrepreneurship on MSME business performance; (2) examine the effect of corporate entrepreneurship on entrepreneurial collaborative capability; (3) examine the effect of entrepreneurial collaborative capability on MSME business performance; also (4) assess the mediating role of entrepreneurial collaborative capability in the relationship between corporate entrepreneurship also MSME business performance.This study adopts a quantitative research design to analyze the relationships also causal effects among variables. The analytical approach employs Structural Equation Modeling (SEM) using the SmartPLS software for data processing also hypothesis testing.